Adapting to change exploring employees’ and leaders’ perspectives on remote work in the post-pandemic era - Aragão, Maria Eugênia Aydar de (2023)
This study aims to understand leaders and employees’ perceptions about the remote work model, which has become a trending topic since the COVID-19 pandemic in 2020, requiring the market to adopt different ways of working in order to keep their business, but bringing challenges when the disease spread was better controlled in 2022. Moreover, it seeks to raise and compile what are the main digital capabilities related to remote work. Finally, this study will also address comparing the public’s points of view about the benefits and drawbacks in adopting remote work. This monograph used a quantitative method to reach its results, as well as bibliographic references collected in some articles published in scientific periodicals. In this project, there were 195 qualified participants in the field research, being 99 responding employees and 96 leaders, in order to analyze the different perceptions of people who lived and/or live the remote work experience, taking into account that some companies may have changed their way of working after the relief of the pandemic, which may distinguish some views. The main points brought up for discussion were the small differences noticed in the study between the two samples and the good practices that can be taken into account when implementing remote work.